Peran Vitamin E pada Kulit - Devitasari, Rizky; Basuki, Santosa (RSUD Dr. Saiful Anwar Province of East Java, 2022)
Vitamin E has many functions for the human body. The role of vitamin E in the skin includes being an antioxidant, maintaining skin moisture, protection against sunlight, and the process of wound healing. Sources of vitamin E can be obtained from vegetable oils, nuts, seeds, meat and milk. Vitamin E deficiency can result from food intake or absorption disorders. Impaired absorption of fat such as cystic fibrosis, Crohn's disease, can cause deficiency because the carrier of vitamin E is fat. This can also affect the protective function of cell membranes against free radicals to influence organ systems. Vitamin E therapy can be both topical and systemic. Topical vitamin E used as a component of skin products has anti-inflammatory and antiproliferative effects in concentrations ranging from 2 to 20%. Vitamin E in oral form is D-α tocopherol, with an oral dose of between 50 IU and 1000 IU per day.